The uropygial gland of the monk parakeet Myiopsitta monachus: Histology, morphogenesis, and evolution within Psittaciformes (Aves). Issue 3 (4th November 2019) - Carril, Julieta; Chiale, María C.; Barbeito, Claudio G.
Abstract: We describe the morphology, histology, and histochemical characteristics of the uropygial gland (UG) of the monk parakeet Myiopsitta monachus . The UG has a heart‐shape external appearance and adenomers extensively branched with a convoluted path, covered by a stratified epithelium formed by different cellular strata and divided into three zones (based on the epithelial height and lumen width), a cylindrical papilla with an internal structure of delicate type and two excretory pores surrounded by a feather tuft. Histochemical and lectin‐histochemical techniques performed showed positivity against PAS, AB pH 2.5, AB‐PAS, and some lectines, likely related to the granivorous feeding habits. Also, we describe the morphogenesis of the UG of the monk parakeet, which appears at embryological stage 34 as a pair of ectodermal invaginations. Heterochronic events in the onset development of the UG when compared with other birds could be recognized. Finally, to examine the phylogenetic occurrence of the UG within the Psittaciformes and infer its evolutionary history, we mapped its presence/absence over a molecular phylogeny. The reconstruction of the characters states at ancestral nodes revealed that the presence of the UG was the plesiomorphic feature for Psittaciformes and its loss evolved independently more than once. Abstract : The uropygial gland (UG) is a skin organ exclusive of birds and highly variable among species. We study for the first time the morphology, histology, histochemical characteristics, development, and evolutionary history of the UG of the monk parakeet ( Myiopsitta monachus, Psittaciformes) in a comparative context. We conclude that (a) the morphology and histology of the UG differs within Psittaciformes; (b) the histochemical reactivity and lectin binding patterns of the UG are likely to be related to the granivorous feeding habits; (c) heterochronic events in the onset development of the UG could be recognized; and (d) the presence of the UG is the ancestral condition for Psittaciformes and its loss evolved five times independently (probably related to the activation/inactivation of genes involved in the formation of the gland). Highlights: First study of the morphology, histology, and histochemical characteristics of the uropygial gland (UG) of the monk parakeet ( Myiopsitta monachus, Psittaciformes, Aves) and the first in‐depth research of the UG of any Psittaciformes. Differences in the onset of the UG formation in the monk parakeet when compared with those of other birds provided evidence for developmental heterochronic events. Presence of the UG is the plesiomorphic condition for Psittaciformes and its loss, which evolved five times independently, is probably related to the activation/inactivation of genes involved in the formation of the gland.